A practical guide to the stereological assessment of glomerular number, size, and cellular composition. Issue 10 (21st January 2020) - Sutherland, Megan R.; Vojisavljevic, Danica; Black, Mary Jane
Abstract: The evaluation of a range of measures in the kidneys, such as developmental stage, rate and success, injury, and disease processes, relies on obtaining information on the three‐dimensional structure of the renal corpuscles, and in particular the glomerular capillary tufts. To do this in the most accurate, comprehensive, and unbiased manner depends on a knowledge of stereological methods. In this article, we provide a practical guide for researchers on how to quantitate a number of structures in the kidneys, including the estimation of total glomerular number, glomerular capillary length and filtration surface area, and the cellular composition of individual glomeruli. Guidance is also provided on how to apply these methods to kidneys at different sizes and levels of maturity.